Experimental investigation of an indirect solar dryer integrated with phase change material for drying valeriana jatamansi (medicinal herb). (September 2017) - Bhardwaj, A.K.; Chauhan, Ranchan; Kumar, Raj; Sethi, Muneesh; Rana, Adit
Abstract: In this study, an experimental investigation of an indirect solar dryer integrated with phase change material has been carried out for drying Valeriana Jatamansi . The experimentation has been performed under the climatic conditions of Himalayan region, Solan (latitude − 30.91°N, longitude − 77.09°E), Himachal Pradesh (India) in the month of October-November 2016. Paraffin RT-42 has been used as a phase change material in the dryer. Using this system, the moisture content of rhizomes reduced from 89% to 9% in 5 days as compared to heat pump drying and shade drying, which took 8 days and 14 days, respectively. Results of present study infer that the drying time using phase change material in this setup has reduced by 37.50% and 64.29% when compared to heat pump drying and shade drying, respectively. The dried rhizomes obtained are of superior quality in terms of colour, texture, aroma and bio-medical constituents. Analyses show that by using present setup, total valepotriates obtained were 3.47% as compared to traditional shade drying which yield 3.31%.